Grand Papa and Ellen Aroon being an account of some of the happy times spent together by Thomas Jefferson and his favorite granddaughter - Monjo, F. N.; Cuffari, Richard 1925-. (New York Dell Publishing, 1974)
Nine-year-old Ellen Wayles Randolph describes her relationship with her grandfather, Thomas Jefferson.
Keywords: Jefferson, Thomas -- 1743-1826 -- Juvenile fiction; Coolidge, Ellen Wayles (Randolph) -- 1796-1876 -- Juvenile fiction; Jefferson, Thomas -- 1743-1826 -- Fiction